Assessment of unterraced and terraced farming system on livestock development in mid-hills of Nepal - Giri, Gopal; Nepali, Dainik B; Shrestha, Bhola S (Journal of Agriculture and Environment, 2014)
The unterraced farming (Pata) system which is being practiced in few districts of mid hills of Nepal was assessed in terms of livestock holding and livestock feed availability against the terraced farming system. Field study and household survey was conducted in Arghakhanchi (representing unterraced/Pata) and Tanahun (representing terraced) farming system by selecting 90 households (HHs) from each districts randomly. The study showed that there was only 1.89 Livestock Unit (LU)/HH in Arghakhanchi as compared to 2.64 LU/HH in Tanahun (p<0.01). Dry matter (DM) output per hectare rainfed upland in Tanahun was 6.09 Metric Ton (MT) whereas it was only 3.82 MT in Arghakhanchi (p<0.01). The farming system of Arghakhanchi has created livestock feed shortage, consequently has compelled farmers to raise least number of animals. Hence unterraced farming system of Arghakhanchi needs correction for better livelihood of people as well as improvement in environmental condition.